Development of a Digital Literacy Assessment Instrument for Junior High School Students Using Zep Quiz Media in Ecoprint Batik Learning - Dika Ning Pratiwi; Julia Astutik; Sri Wahyuni (Yayasan Darussalam Bengkulu, 2026)
Digital literacy has become an essential competency for students in the 21st century, particularly in science learning that integrates technology and contextual learning resources. However, appropriate assessment instruments to measure students’ digital literacy skills are still limited. This study aimed to develop a valid and reliable instrument for assessing junior high school students’ digital literacy skills using Zep Quiz media in the context of ecoprint batik learning. The research employed a Research and Development (R&D) method using the Borg and Gall model, which was modified into several stages: problem analysis, planning, product design, expert validation, product revision, small-scale testing, operational revision, and large-scale testing. The participants of this study were 125 junior high school students. Data were collected through observation, questionnaires, and digital literacy assessment tests. The results of expert validation indicated that the developed instrument was highly valid. Item validity analysis showed that all test items met the validity criteria. Furthermore, the reliability coefficient of the multiple-choice test in the large-scale trial reached 0.762, which is categorized as high reliability. These findings indicate that the developed instrument is valid, reliable, and feasible to measure students’ digital literacy skills in science learning using Zep Quiz media integrated with ecoprint batik materials.